Technical efficiency for venezuelan public universities through data analysis model DEA envelopes (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2013)
This research is part of the area of organizational efficiency and Venezuelan higher education sector, whose design was descriptive literature, the overall objective being to develop the theory of technical efficiency Venezuelan public universities through the DEA model, based on some background on Technical Efficiency in education, as well as describing the higher education sector in the country. The conceptual basis reflects the theoretical aspects of technical efficiency and its components being pure technical efficiency, scale efficiency and Model Enclosures Data Analysis DEA mentioning some strengths and limitations, in the latter highlights the difficulties associated with obtaining official data from the Ministry of Popular Power for Higher Education, the National Council of Universities and the Office for University Sector Planning, governing bodies in the country. It examines the input and output variables best suited to the study of technical efficiency in the sector according to the DEA model. Finally, there are conclusions, among which the feasibility of calculating the Technical Efficiency in the sector according to the DEA model, although there are difficulties in establishing a homogeneous sample given the diversity of existing public institutions.
Keywords: technical efficiency; model DEA; venezuelan public universities